Unveiling the concealed: Variation of Condyle, Coronoid & Sigmoid Notch in the local population of Pakistan - Sufyan Ahmed, Qurat Ul Ain, Zainab Qasim Butt, Saqlain Bin Syed Gilani, Faisal Shafiq Malik, Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The objective of this study was to evaluate different morphological variations of coronoid, condyle and sigmoid notch using digital panoramic radiographs. Methods: The study comprised of 409 orthopantomograms (OPG). The different shapes of condyle, coronoid and sigmoid notch was traced and recorded. Both sides were recorded. The data was then subjected to statistical analysis using SPSS 21. Results: The most common variation for condylar process was angled, whereas for coronoid process it was round. Wide shape sigmoid notch was the most common type reported. No statistical difference in right and left coronoid and sigmoid notch was present. Conclusion: The variation in shape of condyle, coronoid and sigmoid notch was found different when compared with different ethnicities. Further studies using a larger group of population can give a further evidence if these OPG’s can be used as a mean of personal identification. Keywords: Forensic odontology, condyle, coronoid, mandible.